Dressed to Marry: Islam, Fashion, and the Making of Muslim Brides in Brazil - Fonseca Chagas, Gisele (Religions, 2019)
This article explores the dress practices of Muslim women in Brazil, focusing on the ways through which they choose, prepare, use, and talk about their wedding garments. The aim is to understand how religiously oriented women interpret the Islamic normative codes concerning the coverage of the female body when managing their appearance, particularly when "special celebrations" such as wedding rituals are involved. How do they combine bridal fashion trends with religious orientations? Drawing on ethnographic fieldwork and personal interviews, this analysis stresses that the desired aesthetic of Muslim women's marital garments unfolds a search for a modest authenticity through which "Brazilian culture", "female beauty", and Islam are mobilized. In conclusion, the study points to the dynamic ways through which this specific encounter of religion and fashion produce an aesthetic based on a degree of improvisation and creativity, since the Islamic fashion industry is absent in the Brazilian market.